The digital health divide: evaluating online health information access and use among older adults - Hall, Amanda K.; Bernhardt, Jay M; Dodd, Virginia; Vollrath, Morgan W (Health Education & Behavior, 2014)
Innovations in health information technology (HIT) provide opportunities to reduce health care spending, improve quality of care, and improve health outcomes for older adults. However, concerns relating to older adults' limited access and use of HIT, including use of the Internet for health information, fuel the digital health divide debate. This study evaluated the potential digital health divide in relation to characteristic and belief differences between older adult users and nonusers of online health information sources. A cross-sectional survey design was conducted using a random sample of older adults. A total of 225 older adults (age range = 50-92 years, M = 68.9 years, SD = 10.4) participated in the study. Seventy-six percent of all respondents had Internet access. Users and nonusers of online health information differed significantly on age (M = 66.29 vs. M = 71.13), education, and previous experience with the health care system. Users and nonusers of online health information also differed significantly on Internet and technology access, however, a large percentage of nonusers had Internet access (56.3%), desktop computers (55.9%), and laptop computers or netbooks (43.2%). Users of online health information had higher mean scores on the Computer Self-Efficacy Measure than nonusers, t(159) = -7.29, p < .0001. This study found significant differences between older adult users and nonusers of online health information. Findings suggest strategies for reducing this divide and implications for health education programs to promote HIT use among older adults.